Solar Based Z Source Inverter for High Power Application - S. Shanmugasundaram (Bulletin of Electrical Engineering and Informatics, 2017)
The different converters are developer in recent years for efficient operation of PV based various controllers for ac load application. The Z source inverter is used as both buck and boost operation. But the proposed paper Z source inverter produce more output voltage than input voltage.  In proposed converter produce high power without using the transformer. The space vector modulation is used as to control the speed of an induction motor. The IFOC based SVM produce the pulse and given to the three phase inverter. In induction motor has high power application so the proposed Z source produces high output. The dc link voltage regulation using the filter. The proposed Z source based PV is implemented using MATLAB/ SIMULINK environment.